Bilateral chylothorax: an unusual complication of cervical rib resection. (January 2015) - Morjaria, Jaymin B.; Aslam, Imran; Johnson, Brian; Greenstone, Michael A.; Kastelik, Jack A.
Bilateral chylothorax is a rare cause of pleural effusions. Here we report an unusual acute presentation of bilateral chylothorax following thoracic outlet surgery. Unique to this case was the disparate characteristics of pleural fluid analyses with an exudate on the left and a transudate on the right. This report describes the recognition and management of bilateral chylothoraces, an uncommon but potentially serious complication of this frequently performed surgical procedure.